The poverty impacts of a WTO agreement - Hertel, Thomas W. (2005)
Describes a major research project on the poverty impacts of a potential Doha agreement. Notes that the best poverty outcome of the Doha Round would require deep cuts in developed countries' agricultural subsidies and tariffs, as well as a reduction of developing country tariffs and a host of complementary domestic reforms.